# Show that the differential equation representing one parameter family of curves (x2 – y2) = c(x2 + y2)2 is (x3 – 3xy2)dx = (y3 – 3x2y)dy.

Given, A differential equation (x3 – 3xy2)dx = (y3 – 3x2y)dy

To Prove: Prove that (x2 – y2) = c(x2 + y2)2

Explanation: We have (x3 – 3xy2)dx = (y3 – 3x2y)dy

Now, Find dy/dx from the given equation Let Put x = λx and y = λy in F(x, y) Taking λ3 as a common from numerator and denominator then,

F(x, y) = λ0F(x, y)

Since, F(x, y) is a homogenous function of degree zero.

Let us Assume , y = vx - - - (ii)

Differentiate equation (i) w.r.t x - - - (iii)

Now, Comparing the equation (i) and (iii), we get Taking x3 as common then, we get     Now, Integrating both sides  Let I = , then

I = log|x| + C

I =  Let 1 - v4 = t

Differentiating , - 4v3 dv = dt

And,  Now, put u = v2

On differentiating w.r.t v    We know,  Putting the values of t       Now, Putting v = y/x       Hence, Proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Interactive Quiz on DIfferential Calculus50 mins  Interactive Quiz on Differential Calculus | Check Yourself56 mins  Functional Equations - JEE with ease48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 